A proliferation‐inducing ligand increase precedes IgA nephropathy recurrence in kidney transplant recipients. Issue 4 (11th March 2019) - Martín‐Penagos, Luis; Benito‐Hernández, Adalberto; San Segundo, David; Sango, Cristina; Azueta, Ainara; Gómez‐Román, Javier; Fernández‐Fresnedo, Gema; López‐Hoyos, Marcos; Ruiz, Juan C.; Rodrigo, Emilio
Abstract: Background: IgA nephropathy (IgAN) may recur in kidney transplant recipients. B‐cell‐activating factor (BAFF), a proliferation‐inducing ligand (APRIL), and α‐defensins are involved in the pathogenesis of native IgAN; however, their role on IgAN recurrence has not been previously analyzed. Methods: Thirty‐five patients with IgAN who received a kidney transplant in our center between January 1, 1993, and December 31, 2015, were included. Recurrence was diagnosed and ruled out in 14 and 11 patients, respectively, by indication biopsies. Pre‐transplant, 6‐month, 1‐, 3‐, and 5‐year sera selected to measure BAFF, APRIL, and defensin by ELISA. Results: Six months post‐transplantation, APRIL levels (300.1 vs 1203.8 pg/mL, P  = 0.033) and the mean APRIL values from 6 months to 3 years (409.8 vs 1258.0 pg/mL, P  = 0.003) were higher in recurrent patients. Both 6‐month APRIL levels (AUC‐ROC 0.753, P  = 0.033) and mean APRIL values (AUC‐ROC 0.844, P  = 0.004) discriminated patients with recurrence risk. By logistic regression, APRIL at 6 months ( P  = 0.044) and mean APRIL ( P  = 0.021) related to the risk of IgAN recurrence independently. Neither BAFF nor defensin related to recurrence. Conclusions: Serum APRIL increased at 6 months and mean APRIL remained higher the first 3 years in patients in whom IgAN was going to recur.